Communicating sexuality education structure and agency at the Ocaña National High School in Carcar City, Cebu, Philippines - Dazo, Jiamaine D.; Sanchez, William Carlo Antonio; Tabada, Ma. Theresa Angelina Q.; Toboso, Peter Jerald L. (Cebu City College of Communication, Art, and Design , University of the Philippines Cebu, 2024)
This study identified and assessed the sustainability of sexuality education in the Philippines, which has long been conflicted by religious factors. Sexuality education in the country exists through the Department of Education?s (DepEd) Comprehensive Sexuality Education (CSE) curriculum, but there are no studies regarding its on-ground integration or communication, such as in confirmed predominantly religious areas like the Ocaña National High School (ONHS) in Carcar City, Cebu. This study is framed by Anthony Giddens? Structuration Theory of organizational communication, which posits that compliance with structures like sexuality education is never guaranteed as individuals always have enough agency to communicate and act according to their own worldviews regardless. Through the Interpretative Phenomenological Analysis (IPA), this qualitative study interviewed key ONHS actors, namely teachers, students, parents, nearby churches and civil society organizations. Results obtained indicate that sexuality education is sustainable, but this sustainability is entirely dependent on the individual beliefs and behaviors being communicated by actors and not necessarily because of the standardization of DepEd. Sexuality education in Carcar is currently prone to sudden socio-cultural developments and ever-changing personal practices, which may detriment its overall objective of alleviating the sexuality-related issues of the Filipino youth.
Thesis (Bachelor of Arts in Communication)--UP Cebu, July 2024.
Includes bibliographical references and appendices.